Sustainable Agricultural Development under the Influence of Technology: A Case Study of Bihar - Sinha, Jitendra Kumar; Sinha, Anurodh Kumar (New Countryside, 2025)
Achieving “Zero Hunger,” one of the core Sustainable Development Goals (SDGs) adopted by the United Nations in 2015, necessitates transformative changes in agricultural systems through sustainable practices and resilient technologies. This study examines the influence of farm technologies and supporting infrastructure on agricultural value-added(GVA) in Bihar, a predominantly agrarian and economically underdeveloped state in India, utilizing time series data from 2000 to 2024. Employing advanced econometric models, dynamic simulations, and impulse response analyses, the research identifies key structural drivers and constraints of agricultural growth in the region. Technological advancement is shown to be a primary driver, with mechanization, improved seed varieties, multi-cropping, and agroforestry practices significantly enhancing land productivity. Capital stock investment exhibits a direct and positive elasticity (0.59%), with its impact persisting up to eight years before diminishing, underscoring the need for periodic reinvestment. Mechanization alone accounts for a 32% contribution to GVA, signalling a transition toward labour-saving technologies. Arable land expansion and sustainable practices also play a pivotal role, contributing 21% to agricultural GVA. Conversely, irrigation infrastructure and chemical fertilizers reveal mixed or negative short-term effects, likely due to inefficient application or ecological constraints. Variables such as labour, credit, forest area, and energy consumption are found to be statistically insignificant. The findings advocate for capital lifecycle management, precision farming, sustainable land use, targeted input application, and credit system reform. The study concludes that an integrated, evidence-based policy framework is essential to ensure sustained agricultural productivity, environmental stewardship, and the long-term realization of SDG-2 in Bihar.